Effectiveness Of Watermelon (Citrullus lanatus) Red Flesh Extract On Reducing Coronary Artery Foam Cells and Thinning Of The Aortical Intima In Wistar Rats (Rattus norvegicus strain Wistar) Atherosclerosis Model - Tiara Lastari; Mochamad Bahrudin; Dian Yuliartha Lestari; Nabila Risma Anjana (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
Introduction: Atherosclerosis (AS) is a process of narrowing of the lumen of arteries due to progressive plaque buildup. Foam Cell and plaque appear as a result of lipoprotein metabolism disorders which result in inflammatory reactions. The incidence of AS in the world is increasing, resulting in various complications that can lead to death. Lycopene is contained in the red flesh of watermelon, which is an antioxidant that can control free radicals and can reduce the risk of AS. Objective: To determine the effectiveness of watermelon (Cittrulus lanatus) red flesh extract on reducing coronary artery foam cells and thinning of the aortic intima in Wistar rats (Rattus norvegicus strain Wistar) atherosclerosis model. Method: This research was an experimental study (true experimental) using the Post Test Only Control Group Design method, which measures the number of coronary artery foam cells and the thickness of the aortic intima in Wistar rats (five groups) after administration of a hypercholesterolemic diet and watermelon red flesh extract at a dose of 250,500,750 mg /kgBW. Data analysis was carried out using One-Way ANOVA and Post Hoc Bonferroni tests. Results: The One-Way ANOVA statistical test showed results of 0.020 for foam cells and 0.008 for thickness of the intimal tunica, which means that there was a real influence of watermelon red flesh extract on decreasing foam cells and significant thinning of the intimal tunica in the treatment group. Furthermore, the Post Hoc Bonferroni test showed that the dose of 750 mg/kgBW had the most effect on reducing foam cells (p=0.046) and thinning the intima (p=0.015). Conclusion: Watermelon (Citrullus lanatus) red flesh extract at a dose of 750 mg/kgBW has a significant effect on reducing the number of foam cells and thinning of the aorta of the Wistar rat model of atherosclerosis.